Associated Factors of Patients’ Survival in Out of Hospital Cardiac Arrest; a Cross-sectional Study - KE, Liang; IEONG, Pui I; E Brock, Kaye; Mpofu, Elias; Yin, Cheng; Feng, Xiuhua; Kou, Pou Kuan; Mok, Chi Kun; Lei, Wai Seng (Archives of Academic Emergency Medicine, 2024)
Introduction: Chinese populations have an increasingly high prevalence of cardiac arrest. This study aimed to investigate the prehospital associated factors of survival to hospital admission and discharge among out-of-hospital cardiac arrest (OHCA) adult cases in Macao Special Administrative Region (SAR), China. Methods: Baseline characteristics as well as prehospital factors of OHCA patients were collected from publicly accessible medical records and Macao Fire Services Bureau, China. Demographic and other prehospital OHCA characteristics of patients who survived to hospital admission and discharge were analyzed using multivariate logistic regression analysis. Results: A total of 904 cases with a mean age of 74.2±17.3 (range: 18-106) years were included (78%>65 years, 62% male). Initial shockable cardiac rhythm was the strongest predictor for survival to both hospital admission (OR=3.57, 95% CI: 2.26-5.63; p<0.001) and discharge (OR=12.40, 95% CI: 5.70-26.96; p<0.001). Being male (OR=1.63, 95% CI:1.08-2.46; p =0.021) and the lower emergency medical service (EMS) response time (OR=1.62, 95% CI: 1.12-2.34; p =0.010) were also associated with a 2-fold association with survival to hospital admission. In addition, access to prehospital defibrillation (OR=4.25, 95% CI: 1.78-10.12; p <0.001) had a 4-fold association with survival to hospital discharge. None of these associations substantively increased with age. Conclusion: The major OHCA predictors of survival were initial shockable cardiac rhythm, being male, lower EMS response time, and access to prehospital defibrillation. These findings indicate a need for increased public awareness and more education.